2018
DOI: 10.1111/srt.12624
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of bound water in skin hydrators prepared with and without a 3D3P interpenetrating polymer network

Abstract: Through the synthesis of a 3D3P-IPN using simplified methods, we were able to increase the water-binding and HA-delivery capabilities of a thin serum. This 3D3P-IPN serum has potential to deliver more hydration to the skin's surface compared to traditional HA formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…This band shifts to lower frequencies in the spectra of diabetic mice D20 and D30 suggesting the These results were confirmed upon the comparison of dielectric constant of the skin. It is known that hyaluronic acid is considered as the gold standard molecule to improve skin hydration [16]. The intense band at 3292 cm -1 is assigned to stretching vibration of vNH groups of proteins and shows that the protein formulation is in the form Amide A [15].…”
Section: Experimental Groupsmentioning
confidence: 99%
“…This band shifts to lower frequencies in the spectra of diabetic mice D20 and D30 suggesting the These results were confirmed upon the comparison of dielectric constant of the skin. It is known that hyaluronic acid is considered as the gold standard molecule to improve skin hydration [16]. The intense band at 3292 cm -1 is assigned to stretching vibration of vNH groups of proteins and shows that the protein formulation is in the form Amide A [15].…”
Section: Experimental Groupsmentioning
confidence: 99%
“…In our case, the lowest concentration assessed was 100 mg/mL for all HAs molecular weights (60, 100, 500 and 1000 kDa). One can argue that concentrations below 50 mg/mL are outside of the MMC zone, but considering the very high water-binding capacity of HA (up to 6 L per g [ 37 , 38 ]), it may be actually possible to act as an MMC agent even at such low concentrations. One cannot also exclude that cell-specific biological events may be at play, considering that, through growth factor interaction and involvement in signalling cascades, sulphated polysaccharides have been shown to enhance the chondrogenic and osteogenic potential of stem cells [ 15 , 49 , 78 ], whilst non-sulphated polysaccharides have been shown to enhance the adipogenic potential of stem cells [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the quest for the ideal MMC agent, hyaluronic acid (HA) was recently utilised in human neonatal fibroblast cultures [ 36 ]. Although this proof of principle study demonstrated the potential of 1500 kDa HA to act as an MMC agent, the optimal HA molecular weight and concentration were not identified and the physicochemical properties (e.g., charge, hydrodynamic radius, polydispersity) were not assessed, which are of significant importance, considering that the effectiveness of HA as an MMC/volume exclusion agent lays on its capacity to bind and retain water molecules (up to 6 L per g) [ 37 , 38 ] in a size-, shape-, concentration- and viscosity-dependent manner [ 39 ]. Herein, we ventured to comprehensively assess the physicochemical properties of different concentrations of different molecular weight HAs in equine adipose-derived stem cell (eADSC) cultures.…”
Section: Introductionmentioning
confidence: 99%
“…The IPN has been shown to restore and sustain hydration content by attracting and binding water molecules more efficiently than traditional cosmetic‐grade forms of HA. Skin that is deeply hydrated by the IPN facilitates the penetration of other actives deeper into the skin and prevents from evaporation leading to an additional moisturization effect . It is also believed that the IPN distributes the delivered actives evenly across the skin surface to enhance light reflection and perceived visual appearance of the skin…”
Section: Discussionmentioning
confidence: 99%
“…Perceptible improvements in skin hydration on the arms and legs were immediate and long‐lasting (eg, dryness, roughness, and smoothness). Benefits related to moisturization (eg, crepiness, texture, and overall appearance) required a longer period to manifest due to an accrual of a more robust lipid layer in the stratum corneum preventing from water evaporation …”
Section: Discussionmentioning
confidence: 99%